Lesbian Transgender (LGBT) Menurut Undang - Undang Nomor 39 Tahun 1999 Tentang Hak Asasi Manusia - Minan Minan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In society, there are terms like Lesbian, Gay, Bisexual, Transgender (LGBT) which are generally considered as a form of sexual orientation deviation. Sexual orientation itself refers to a person's emotional, physical, or romantic attraction to either the same or the opposite sex. Some countries legalize homosexual life, including same-sex marriage, but in the context of sexual deviation, homosexuality is considered contrary to the norms and values maintained in society. Based on this, several issues are raised, namely how Indonesian criminal law, especially the Criminal Code (KUHP), regulates LGBT; looking at Law Number 39 of 1999 concerning Human Rights for LGBT; and what legal efforts are made by the government to address issues related to LGBT. The author uses a descriptive analytical research method, with a normative descriptive approach that examines literature and regulations using qualitative legal analysis. The research results show that the provisions regarding homosexuality in Indonesian criminal law, which include Lesbian, Gay, Bisexual, and Transgender, are contained in Book II of the Criminal Code, Chapter XIV concerning Sexual Crimes, Article 292, and for cases involving children, are stipulated in Article 82 paragraph (1) of Law Number 35 of 2014. Furthermore, there is no legal recognition of homosexuality, and the law only permits homosexual practices involving children under the age of majority. The constitution recognizes human rights with limitations that may not conflict with regulations, morals, religious values, or public safety. The government is making efforts by coordinating not only with the LGBT community but also with relevant agencies, preventing violations arising from policies or systems, and continuously raising awareness among the government, the public, and various parties regarding human rights principles.